2020
DOI: 10.3991/ijim.v14i13.14493
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Acceptance of Padlet as a Microblogging Platform for Writing Skills

Abstract: <p class="Abstract">This research is intended to answer the question, how are the students' perceptions of internet technology in learning and how is the acceptance of Padlet as a <em>microblogging </em>platform for writing skills in German language level A2-B1 CEFR standards for the student. In summary, 21 students within the range of 19-22 years participated, which consisted of 2 males and 19 females - data obtained through opened and closed questionnaires. The results of data analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…It is also shown through previous studies, such as the study by Saetra (2021) and Ab Hamid et al (2019) that there are positive attitudes among students towards the use of Padlet in learning. However, the results of Kharis et al(2020) showed negative attitudes among students and their unwillingness to use Padlet in learning writing skills due to technological and technical reasons.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…It is also shown through previous studies, such as the study by Saetra (2021) and Ab Hamid et al (2019) that there are positive attitudes among students towards the use of Padlet in learning. However, the results of Kharis et al(2020) showed negative attitudes among students and their unwillingness to use Padlet in learning writing skills due to technological and technical reasons.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 97%
“…The teacher and his students are then allowed to participate by sending them the Padlet link to enable interaction between the student and teacher, with the student double-clicking on (+) in the padlet wall and replying to the teacher; participation is either through written texts or notes or attaching multimedia, answer files or link Via the same page that the student has opened. The teacher can easily export this work after its completion in the form of images or files (PDF, CSV, EXCEL) and share it with students or with other teachers (Al-Zahrani, 2018;Kharis, Dameria & Ebner, 2020). Padlet application is characterized by the ability to create a virtual wall with attractive backgrounds on which everything related to the topic of the wall, including images, notes, links and multimedia can be installed.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Web-based CALL is among the common tools utilized during video conferencing. In this research, the researchers investigated the students' perceptions toward the use of one of the famous CALL tools, Padlet as an online virtual wall, where lecturers and students can share, reflect, and collaborate on a platform called Padlet (Kharis, Dameria, et al, 2020). In addition, (Etfita & Wahyuni, 2020) mention that Padlet is a web-based interactive tool that can be used to facilitate communication between lecturers and students and that a Padlet wall can contain an unlimited number of postings, with collaborators able to comment, share, and create posts for a variety of purposes without requiring an account (Dianati et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martins et al (2019) sostienen que los recursos informáticos en espacios educativos se han promovido e integrado gracias a las TIC. Kharis et al (2020) por la amplitud de estos recursos de microblogging, ponen de manifiesto, que el Padlet sería una aplicación que puede favorecer al pensamiento crítico. Sobre este tipo de pensamiento, Maturana y Lombo (2020) sugieren que este, no se puede enseñar de forma abstracta en un ambiente poco común en el estudiante, sino que debe tener lugar en contextos prácticos.…”
Section: Introductionunclassified